Berry phases in electronic structure theory - Vanderbilt, David (CAMBRIDGE UNIVERSITY PRESS United Kingdom, 2018)
"Over the past 25 years, mathematical concepts associated with geometric phases have come to occupy a central place in our modern understanding of the physics of electrons in solids"--
Keywords: Electronic structure; Geometric quantum phases; Quantum electronics; Electronics